2016
DOI: 10.1038/srep28708
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating the Independent Influence of Cell Adhesion and Spreading Area on Stem Cell Fate Determination Using Micropatterned Surfaces

Abstract: Adhesion and spreading are essential processes of anchorage dependent cells involved in regulation of cell functions. Cells interact with their extracellular matrix (ECM) resulting in different degree of adhesion and spreading. However, it is not clear whether cell adhesion or cell spreading is more important for cell functions. In this study, 10 types of isotropical micropatterns that were composed of 2 μm microdots were prepared to precisely control the adhesion area and spreading area of human mesenchymal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 58 publications
2
60
0
Order By: Relevance
“…Indeed multinucleated cells plated on planar substrates always have larger cell projected areas than their mononucleated counterparts 31 . The interrelationship between the cell projected area and organization of the actin cytoskeleton, development of traction forces and assembly of focal adhesions was observed in many prior studies [18][19][20][32][33][34] . Therefore, the optimal development of the actin cytoskeleton requires a sufficient spreading area that could be different for different cell types.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Indeed multinucleated cells plated on planar substrates always have larger cell projected areas than their mononucleated counterparts 31 . The interrelationship between the cell projected area and organization of the actin cytoskeleton, development of traction forces and assembly of focal adhesions was observed in many prior studies [18][19][20][32][33][34] . Therefore, the optimal development of the actin cytoskeleton requires a sufficient spreading area that could be different for different cell types.…”
Section: Discussionmentioning
confidence: 76%
“…A number of studies have found that geometry and size of adhesive islands determine a variety of different aspects of cellular organization and function [16][17][18][19][20] . Therefore, in search of external factors that may determine the self-organization of the actin cytoskeleton we first investigated the effect of a basic scaling parameter, cell projected area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al () reported that controlling cell shape on micropatterned substrates led to an increase in cytoskeletal tension and augmented BMP‐2‐induced osteogenesis. Other studies, however, have indicated that it is adhesion strength and not cell shape that drives osteogenesis (Khetan et al, ; Wang et al, ). Furthermore, cytoskeleton tension has been shown to be higher when the cells are encapsulated in degradable hydrogels compared with non‐degrading hydrogels, despite having the same amount of adhesion peptides (Khetan et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…For example, Wang et al (2012) reported that controlling cell shape on micropatterned substrates led to an increase in cytoskeletal tension and augmented BMP-2-induced osteogenesis. Other studies, however, have indicated that it is adhesion strength and not cell shape that drives osteogenesis (Khetan et al, 2013;Wang et al, 2016).…”
mentioning
confidence: 98%
“…43 The cells bind to ECM components adsorbed at the material surface through integrin receptors, which upon clustering form focal adhesions that represent a structural link between the cytoskeleton and the biomaterial surface. 44 The cell adhesion and spreading of human kidney (HK-2) cells were studied on the different supramolecular surfaces prior to and after modification with the PEG-BCN hydrophilic ) on the modified surfaces. All the data represented in the graph results from visco-elastic modeling using a Voigt-Voinova model.…”
Section: Cell Adhesion Studiesmentioning
confidence: 99%